2017
DOI: 10.3892/ol.2017.6876
|View full text |Cite
|
Sign up to set email alerts
|

Expression of circadian clock genes in human colorectal adenoma and carcinoma

Abstract: Circadian rhythms are fundamental biological systems in most organisms. Epidemiological and animal studies have demonstrated that disruption of circadian rhythms is linked to tumor progression and mammalian tumorigenesis. However, the clinical significance of in situ clock gene expression in precancerous and cancerous colorectal lesions remains unknown. The present study aimed to investigate mRNA transcript levels of circadian clock genes within human colorectal cancer and adenoma tissue sections. Using in sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 21 publications
3
30
0
1
Order By: Relevance
“…In the current study, CK1ε was downregulated in DEN‐treated mice, as it occurred with Per and Cry, while Bmal1, Clock, and Npas2 genes were upregulated. These data are in agreement with previous research which has shown a changed expression of CK1ε in parallel to the disrupted profile of other circadian clock genes in gastric cancer or human colorectal carcinoma . Melatonin treatment resulted in a CK1ε upregulation that could contribute to its protective effect.…”
Section: Discussionsupporting
confidence: 93%
“…In the current study, CK1ε was downregulated in DEN‐treated mice, as it occurred with Per and Cry, while Bmal1, Clock, and Npas2 genes were upregulated. These data are in agreement with previous research which has shown a changed expression of CK1ε in parallel to the disrupted profile of other circadian clock genes in gastric cancer or human colorectal carcinoma . Melatonin treatment resulted in a CK1ε upregulation that could contribute to its protective effect.…”
Section: Discussionsupporting
confidence: 93%
“…The retrospective analysis of patients with breast cancer also indicates that low expression of PER2 is associated with poor prognosis. The role of clock genes in controlling the sensitivity of cancer cells to chemotherapeutic drugs has been demonstrated by the overexpression of Bmal1 (39), loss of Cry1/2 (40), and down-regulation of Per2 (41). The modulation of chemosensitivity of cancer cells by clock genes is closely related to their ability to regulate cell-cycle progression and apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…127 In vivo and in vitro studies have demonstrated that disruption of circadian rhythms is linked to tumour progression and mammalian tumorigenesis for several malignancies such as liver cancer, 128 oral squamous cell carcinoma, 129 gastric, pancreatic and colorectal carcinoma. 130 Clock genes contribute to the occurrence and development of tumours by regulating and interfering with oncogenes (c-myc), tumoursuppressor genes (P53 and P21), genes involved in the regulation of the cell cycle and vascular endothelial growth factor. These target genes regulated by the biological clock genes are involved in DNA damage repair, cell proliferation and apoptosis.…”
Section: Clock Genes and Cancermentioning
confidence: 99%